Secretory carcinoma of the parotid gland in a pediatric patient: an unusual report and literature update - Maciel, Tayná Figueiredo; Brandão, Sílvia Cristina Oliveira; Maia, Maiko Ramos; Câmara, Jeconias; Libório-Kimura, Tatiana Nayara; Cunha, Renata Gualberto da (Journal of Oral Diagnosis, 2025)
A 16-year-old male patient exhibited a nodular lesion measuring 5.0 centimeters in its greatest diameter in the right parotid gland. This lesion had been present for a period of two years, without any associated symptoms. Upon palpation, the lesion was characterized as demarcated, firm, and painless. The patient underwent surgical excision, and the initial hypothesis was that the lesion was a pleomorphic adenoma (PA). Microscopically, the tumor exhibited a variable growth pattern between cribriform and micropapillary areas, with neoplastic cells positive for mammaglobin, S-100, and Pan-Trk. Immunohistochemistry was employed to substantiate the diagnosis of secretory carcinoma (SC). Two years following the surgical intervention, no signs of recurrence or complications have been observed. Although rare, secretory carcinoma (SC) in pediatric patients has been documented in the literature and can mimic benign neoplasms due to its mild characteristics.